Weathering of till in northern Sweden and its implications for the geochemistry of soil water, groundwater and stream water - Land, Magnus (Luleå tekniska universitet, 1998)
Natural exogenic geochemical processes in northern Sweden have been studied. The thesis is focused on field weathering rates and variations in the chemical composition of water with time and space. Variations in weathering rates of silicate minerals are important for the global CO2 cycle, and thus also for climatic changes. Soil, soil water, groundwater, and stream water samples have been collected and analyzed. Complementary to the field studies, leaching experiments in the laboratory have also been performed. The results indicate that the release rates of SiO2, Al2O3, Fe2O3, K2O and Na2O due to weathering of till have decreased during the past 8700 years. The release rates of CaO and MgO appear to have increased. Chemical weathering of till is important for the chemical composition of soil water, groundwater and stream water in northern Sweden. Special emphasis is given to the mobility of heavy metals and rare earth elements during weathering. Godkänd; 1998; 20061122 (haneit)